Ekologi dan Hadits: Analisis tentang Peran Manusia sebagai Khalifah di Bumi - Syauqi, M.; Askar, Romlah Abubakar; Ghofur, Abdul (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to explore the role of humans as stewards (khalifah) on Earth from the perspective of the hadiths of Prophet Muhammad (peace be upon him) and its implications for ecological awareness. Using a literature review approach, this research analyzes a number of hadiths related to the environment that reflect the Prophet’s concern for nature. The findings reveal that these hadiths contain important messages about environmental preservation, prohibitions against causing destruction, and calls for frugality and care for other living beings. The concept of khalifah in Islam positions humans as bearers of Allah’s trust to care for and manage the Earth with principles of justice, balance, and sustainability. This study affirms that Islamic environmental ethics are highly relevant as both a theological and practical foundation for addressing the current global ecologica lcrisis.